Isolation and Characterization of cDNA encoding chalcone synthase from flower buds of orchid Dendrobium variety sonia 17 - Anjana G R (Department of Plant Biotechnology, College of Agriculture, 2007)
The study entitled “Isolation and characterization of cDNA encoding chalcone synthase gene from the flower buds of orchid Dendrobium variety Sonia 17” was conducted at the Department of Plant Biotechnology, Vellayani, Thiruvananthapuram during the period from 2005 to 2007 with an objective of studying the isolation and characterization of cDNA encoding chalcone synthase gene involved in anthocyanin pigmentation in orchid flower buds. . Heterologous forward and reverse primers were designed based on the gene sequences of Oryza sativa, Fragaria ananasa and Phalaneopsis orchid using primer3 software. Total RNA was isolated from immature floral tissues using hot phenol method which gave an yield of 80 - 200 μg g -1 of the tissue and a A260/A280 ratio ranging between 1.6 –2.0. Messenger RNA was purified from the total RNA using the mRNA purification kit from GENEI (Bangalore). Reverse transcription-polymerase chain reaction was carried out to study the expression of gene. The RT-PCR amplified products representing chalcone synthase (CHS) gene was eluted and purified. The product was sequenced and studied the similarity of the same using homology search. All sequenced regions were subjected to BLASTN and BLASTX similarity search. Rice chalcone synthase specific primer produced an amplified sequence of 460 bp long and showed maximum similarity to the cDNA clone 5', mRNA sequence of. flower bud of Phalaenopsis violacea and flower bud of Phalaenopsis equestris Lambda ZapII cDNA Library in BLASTN similarity search.BLASTX analysis of the sequence showed similarity to maturase K protein of Aerangis kirki. The cDNA amplified with strawberry chs specific primer showed maximum similarity to the cDNA clone 5’, mRNA sequence of Phalaenopsis violacea flower bud and flower bud of Phalaenopsis equestris in the BLASTN similarity search. BLASTX analysis of the sequence showed similarity to LFY-like protein of Serapias lingua. The results of the nucleotide to nucleotide search (BLASTN) of the cDNA of orchid, amplified using chalcone synthase specific primer from orchid showed similarity to cDNA 5', mRNA sequence of Ipomoea batatas in the BLASTN similarity search. BLASTX analysis of the sequence showed similarity to retrotransposon protein of Oryza sativa (japonica cultivar-group). The result of the sequences obtained from the study shows similarity with the genes involved in the biosynthetic pathway of Phalaenopsis orchid flower fragrance.